History of Russian Reception of Drama I.-V. Goethe’s “Torquato Tasso” - D. N. Zhatkin; N. L. Vasiliev (Научный диалог)
The history of Russian translations of the I.-V. Goethe’s drama “Torquato Tasso” (1789) is discussed in the article. Responses testifying to the familiarity with this work of many Russian writers, in particular, V. A. Zhukovsky, N. V. Kukolnik, N. A. Polevoy, I. V. Kireevsky, N. I. Nadezhdin, I. S. Turgenev, A. I. Herzen and others are systematized. The history of Russian Reception of the “Torquato Tasso”, dating back to the 1840s (A. N. Strugovschikov, N. M. Satin, A. N. Yakhontov, etc.), and its influence on aesthetic reflection in the era of romanticism and afterwards is discussed in the article. Particular attention is paid to the previously unknown translation of V. G. Benediktov (presumably the 1850s), preserved in the archives of the writer in the Russian National Library. Subsequent translations created by V. A. Sorgenfrey (1920-1921) and S. M. Soloviev (1933) are also analyzed. With the involvement of diary, epistolary and memoir materials, the activity of A. A. Blok as a translation editor by V. A. Sorgenfrey is conceptualized. The relevance of the study is due to the need to clarify the large-scale picture of the translation and literary critical reception of the West European classics in Russia.